A Novel Small Molecule Which Increases Osteoprotegerin Expression and Protects Against Ovariectomy-Related Bone Loss in Rats - Han, Xiaowan; Gong, Shiqiang; Li, Ni; Wang, Xiao; Liu, Peng; Xu, Yanni; He, Xiaobo; Jiang, Wei; Si, Shuyi (Frontiers in Pharmacology, 2019)
The ratio of osteoprotegerin (OPG) to the receptor activator of NF-κB ligand (RANKL) is a key determinant in the regulation of bone metabolism. The study was performed to screen novel anti-osteoporotic drugs regulating OPG/RANKL ratio and evaluate their effect on bone metabolism. According to the screening results and in vitro results, we found a small molecule, E09241, significantly increased the ratio of OPG/RANKL by mainly increasing OPG expression. Our in vitro studies showed that E09241 increased the alkaline phosphatase activity of mouse osteoblasts, promoted mineralization, and increased the expression of osteogenic differentiation-related genes. In addition, we observed that E09241 inhibited RANKL-induced osteoclast differentiation and reduced the expression of osteoclast differentiation-related proteins nuclear factor of activated T cells c1 (NFATc1) and matrix metalloproteinase 9 (MMP-9). More importantly, E09241 exerted therapeutic protection against bone loss in ovariectomized rats in vivo. This protective effect was confirmed to be achieved by inhibiting bone resorption and promoting bone formation in vivo. Mechanistically, E09241 regulates OPG expression through canonical Wnt/β-catenin signaling. Our findings suggest that E09241 is a promising small-molecule compound for treating osteoporosis with a dual effect on osteoblasts and osteoclasts.